Traditional care and alternative therapies for pregnant women: a comparative review - Karim, Farhana S.; Maharana , Satyapriya (International Journal Of Community Medicine And Public Health, 2024)
Traditional care and alternative therapies are gradually becoming prevalent in the era of pharmaceutical medicine. Pregnant women are now using more of the traditional therapies because of the increasing acceptance, notably after the COVID-19 outbreak, to handle pregnancy issues such as morning sickness, anxiety, and pain naturally and holistically. The article includes some of the most popular traditional and alternative treatments, which include yoga, ayurveda, herbal treatment, acupressure, reflexology, massage therapy, moxibustion plus music and dance therapy, as well as aromatherapy, hypnotherapy homeopathy, and reiki. Patients will require knowledge of what each one of them has to benefit them when they use them during pregnancy since not all could be safe or even helpful while expecting a baby. A well-known fact in the literature today is an increasing reliance on traditional treatments, which is considered risk-free compared to conventional medicine, enhancing physical and psychological well-being. The paper is a basic guide to pregnancy management that may involve using traditional and alternative medicines, which have been proved by research. If these care and therapies are accompanied by good medical advice on issues concerning the wellness of the unborn child and its mother in general, will help to ease their pregnancy journey.